Anticoagulant Therapy in Difficult Patients with Atrial Fibrillation: When the Risks of Embolism and Bleeding Are Comparable - D. A. Napalkov (Racionalʹnaâ Farmakoterapiâ v Kardiologii, 2018)
This article affects  the problems of using NOAC in the most defenseless groups  of patients with atrial fibrillation: those  who have high bleeding and high thromboembolic risk and elderly. The focus is on comparison of effectiveness and safety of NOACs based  on randomized clinical trials (RCT) and real-world data (RWD). The possible reasons for the different interpretation of the data of the RCT and the RWD are shown. Use of NOAC in reduced doses prescribing according to RCT and RWD are shown. Our own 13-month observation of patients 75 years and older with very high thromboembolic risk (CHA2DS2-VASc – 4,5  points) on rivaroxaban therapy are presented. Good efficacy and  safety  of full and  reduced doses  of rivaroxaban were demonstrated: only 2 episodes of small bleedings and no large bleedings (ISTH criteria) were detected as well as no thromboembolic events.  Thus, even difficult patients with AF and comorbidity may be safely and effectively treated with NOACs taking into consideration integrated approach and correction of modifiable risk factors.